2014
DOI: 10.5194/os-10-107-2014
|View full text |Cite
|
Sign up to set email alerts
|

Fate of colloids during estuarine mixing in the Arctic

Abstract: Abstract. The estuarine behavior of organic carbon (OC) and trace elements (TE) was studied for the largest European sub-Arctic river, which is the Severnaya Dvina; this river has a deltaic estuary covered in ice during several hydrological seasons: summer (July 2010, 2012) and winter (March 2009) baseflow, and the November–December 2011 ice-free period. Colloidal forms of OC and TE were assessed for three pore size cutoffs (1, 10, and 50 kDa) using an in situ dialysis procedure. Conventionally dissolved (<… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 126 publications
6
26
2
1
Order By: Relevance
“…These results are in accordance with previous studies suggesting that OC derived from erosion of thawing permafrost may have short residence times in the surface water and quickly settle to the sea floor Vonk et al, 2010aVonk et al, , 2010b. This data are in agreement with previous studies showing the important role of iron oxides in the transfer of dissolved OC (DOC) from the water column to the sediment [Barber et al, 2014;Gustafsson et al, 2000;Ingri et al, 2004;Pokrovsky and Schott, 2002;Pokrovsky et al, 2014;Riedel et al, 2013;Tipping, 1981]. Chlorophyll and particulate Fe have also been reported to be correlated in sub-Arctic water columns [Gelting et al, 2010].…”
Section: Quantitative Source Apportionment Of Sedimentary Oc Versus Osupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in accordance with previous studies suggesting that OC derived from erosion of thawing permafrost may have short residence times in the surface water and quickly settle to the sea floor Vonk et al, 2010aVonk et al, , 2010b. This data are in agreement with previous studies showing the important role of iron oxides in the transfer of dissolved OC (DOC) from the water column to the sediment [Barber et al, 2014;Gustafsson et al, 2000;Ingri et al, 2004;Pokrovsky and Schott, 2002;Pokrovsky et al, 2014;Riedel et al, 2013;Tipping, 1981]. Chlorophyll and particulate Fe have also been reported to be correlated in sub-Arctic water columns [Gelting et al, 2010].…”
Section: Quantitative Source Apportionment Of Sedimentary Oc Versus Osupporting
confidence: 92%
“…Chlorophyll and particulate Fe have also been reported to be correlated in sub-Arctic water columns [Gelting et al, 2010]. This data are in agreement with previous studies showing the important role of iron oxides in the transfer of dissolved OC (DOC) from the water column to the sediment [Barber et al, 2014;Gustafsson et al, 2000;Ingri et al, 2004;Pokrovsky and Schott, 2002;Pokrovsky et al, 2014;Riedel et al, 2013;Tipping, 1981].…”
Section: Quantitative Source Apportionment Of Sedimentary Oc Versus Osupporting
confidence: 89%
See 1 more Smart Citation
“…REE behave almost conservative in organic-rich systems [31] and only a small percentage of the suspended particles and colloids are trapped in the estuary [31,49], while the remaining particles and colloids enter the open oceans. In marked contrast, in systems dominated by inorganic particles, REE behave non-conservatively [31,46,47,50] and >98% of the suspended material is trapped in the estuary [46,51]. Rousseau et al [50] showed that leached particulate REE from the Amazonas river contribute significantly to the dissolved REE budget and the Nd isotopic composition of the modern oceans, indicating that riverine REE input is an important source for the global modern oceans and its Nd isotope compositions.…”
Section: Riverine Inputmentioning
confidence: 99%
“…In some studies it was claimed that riverine DOM behaves conservatively, which means that DOM is a simple dilution and DOM concentration decreases linearly with increases in water salinity (Pokrovsky et al, ; Stein et al, ). A negligible increase in DOM concentrations at low salinity is considered to be an outlier of measured values and is not considered (Köhler et al, ).…”
Section: Introductionmentioning
confidence: 99%